Capital Structure and Firm Performance in Nigerian-Listed Companies - Abata, Matthew Adeolu; Migiro, Stephen Oseko (Journal of Economics and Behavioral Studies, 2016)
a number of business failures have not been reported in Nigeria arising from inability to payback nor does service debts .This paper empirically investigate the relationship between capital structure and firm performance in the Nigerian listed firms. A sample of 30listed firms out of a population of 173 were examined from 2005 to 2014 using multiple regression tools. Two hypotheses were formulated and tested using descriptive statistics and an econometric panel data technique to analyze the gathered data. An insignificantly negative correlation was found between financial leverage and ROA on one hand and a significantly negative relationship between debt/equity mix and ROE on the other hand. It is therefore recommended that firms should use long term liabilities to finance firm’s activities and mix debt/equity appropriately by ensuring that debt financing ratio is lower to enhance corporate performance and survival.